The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15586/aei.v49i5.464
|View full text |Cite
|
Sign up to set email alerts
|

Coniferyl aldehyde alleviates LPS-induced WI-38 cell apoptosis and inflammation injury via JAK2–STAT1 pathway in acute pneumonia

Abstract: Pneumonia is a kind of inflammatory disease characterized by pathogen infection of lower respiratory track. Lipopolysaccharide (LPS) is the main bioactive component of Gram-negative bacteria responsible for inflammatory response. Recently, coniferyl aldehyde (CA) has been reported to play a crucial role because of its anti-inflammatory activity. However, the effect and mechanisms of CA in ameliorating symptoms of acute pneumonia remain unknown. Evaluating and identifying the value and exploring the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We established the inflammatory model using WI-38 cells challenged by LPS, reflected by increase of proinflammatory cytokines and decrease of anti-inflammatory cytokine, which was consistent to previous reports (He et al, 2021;Yang et al, 2021). A previous report suggested that sinomenine could reduce the inflammation in macrophages (Zeng & Tong, 2020).…”
Section: Gstm1 Upregulation Reverses the Influences Of Sinomenine On ...supporting
confidence: 88%
See 1 more Smart Citation
“…We established the inflammatory model using WI-38 cells challenged by LPS, reflected by increase of proinflammatory cytokines and decrease of anti-inflammatory cytokine, which was consistent to previous reports (He et al, 2021;Yang et al, 2021). A previous report suggested that sinomenine could reduce the inflammation in macrophages (Zeng & Tong, 2020).…”
Section: Gstm1 Upregulation Reverses the Influences Of Sinomenine On ...supporting
confidence: 88%
“…Similarly, our study found that sinomenine blunted the inflammation in WI‐38 cells challenged by LPS, indicating its anti‐inflammatory role in WI‐38 cells. Lung cell apoptosis is also an important property in LPS‐induced pediatric pneumonia model (He et al, 2021; Wang, Zhang, & Chen, 2021; Wang, Zhang, Zhao, & Dai, 2021; Yang et al, 2021). Consistent to these reports, this research also found the increased apoptosis in LPS‐challenged WI‐38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were planted in 96‐well plates and then treated according to the experimental requirements 26 . To study cell viability, 10 μL of Cell Counting Kit 8 (CCK8) solution (Goodbio Technology, Wuhan, China) was added to the treated cells and then incubated in an incubator for 1 h. After being put into a microplate meter, the absorbed light was detected at 450 nm, and the cell viability was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were planted in 96-well plates and then treated according to the experimental requirements. 26 To study cell viability, 10 μL of Cell…”
Section: Cell Counting Kit 8 Assay and Cell Proliferationmentioning
confidence: 99%
“…Cells were seeded at a density of 5 × 10 3 cells per well into 96-well plates. As previously described [23], 10 µL of CCK-8 reagent (cat. no.…”
Section: Cell Counting Kit-8 (Cck-8) Detectionmentioning
confidence: 99%